The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5144/0256-4947.2014.217
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of maturity onset-diabetes of the young caused by hepatocyte nuclear factor-4 alpha mutation: red flags for prediction of the diagnosis

Abstract: BACKGROUND AND OBJECTIVESThe prevalence of maturity-onset diabetes of the young (MODY) in Saudi population remains unknown, and data on molecular etiology of this condition is limited. Therefore, the present study was undertaken to elucidate clinical and molecular characteristics of a Saudi family with MODY 1.DESIGN AND SETTINGSThis is a case series study conducted at Saad Specialist Hospital in Alkhobar, Saudi Arabia.PATIENTS AND METHODSA 12-year-old female presented to us with symptoms suggestive of diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Studies on MODY in children are scarce in the MENA region, mainly due to misdiagnosis as type 1 or type2 diabetes. A study in Saudi Arabia reported MODY 1 in five members of a family; however, the overall prevalence of MODY in Saudi Arabia is unknown 37 . Another study from Iran studied 12 families with a history of diabetes and reported HNF4A mutations causing MODY1 in 26.6% of the patients, which is considered significant 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on MODY in children are scarce in the MENA region, mainly due to misdiagnosis as type 1 or type2 diabetes. A study in Saudi Arabia reported MODY 1 in five members of a family; however, the overall prevalence of MODY in Saudi Arabia is unknown 37 . Another study from Iran studied 12 families with a history of diabetes and reported HNF4A mutations causing MODY1 in 26.6% of the patients, which is considered significant 38 .…”
Section: Discussionmentioning
confidence: 99%